The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1152/ajpcell.2001.280.4.c859
|View full text |Cite
|
Sign up to set email alerts
|

KCNQ4 channels expressed in mammalian cells: functional characteristics and pharmacology

Abstract: Human cloned KCNQ4 channels were stably expressed in HEK-293 cells and characterized with respect to function and pharmacology. Patch-clamp measurements showed that the KCNQ4 channels conducted slowly activating currents at potentials more positive than -60 mV. From the Boltzmann function fitted to the activation curve, a half-activation potential of -32 mV and an equivalent gating charge of 1.4 elementary charges was determined. The instantaneous current-voltage relationship revealed strong inward rectificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
62
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 30 publications
10
62
1
Order By: Relevance
“…Linopirdine and its more potent analog XE991 have been useful in the study of heterologously ex- M. Although linopirdine and XE991 also block other voltagedependent currents (5,26,38), they do so at higher concentrations (IC 50 Ͼ100 M). We found that the M-type current in RPE cells was quite sensitive to block by linopirdine, with an apparent IC 50 of 0.5 M. Consistent with our previous finding (41), XE991 was also effective, with an apparent IC 50 of 0.3 M. The IC 50 values for the block of the M-type current by linopirdine and XE991 are similar to those of KCNQ1, with IC 50 for block of 9 and 0.8 M, respectively (35), but are about an order of magnitude lower than those of homomeric KCNQ4 and KCNQ5 channels, with IC 50 of 6 -14 and 16 -75 M, respectively (18,27,30). This would seem to argue against the involvement of KCNQ4 or KCNQ5 channels in the M-type current and in favor of KCNQ1, but it is possible that the M-type channel sensitivity to these blockers is influenced by interactions with KCNE subunits or other factors.…”
Section: Discussionmentioning
confidence: 88%
“…Linopirdine and its more potent analog XE991 have been useful in the study of heterologously ex- M. Although linopirdine and XE991 also block other voltagedependent currents (5,26,38), they do so at higher concentrations (IC 50 Ͼ100 M). We found that the M-type current in RPE cells was quite sensitive to block by linopirdine, with an apparent IC 50 of 0.5 M. Consistent with our previous finding (41), XE991 was also effective, with an apparent IC 50 of 0.3 M. The IC 50 values for the block of the M-type current by linopirdine and XE991 are similar to those of KCNQ1, with IC 50 for block of 9 and 0.8 M, respectively (35), but are about an order of magnitude lower than those of homomeric KCNQ4 and KCNQ5 channels, with IC 50 of 6 -14 and 16 -75 M, respectively (18,27,30). This would seem to argue against the involvement of KCNQ4 or KCNQ5 channels in the M-type current and in favor of KCNQ1, but it is possible that the M-type channel sensitivity to these blockers is influenced by interactions with KCNE subunits or other factors.…”
Section: Discussionmentioning
confidence: 88%
“…All other chemicals were purchased from Sigma Aldrich. HEK293 cells stably expressing Kv7.4 were a gift from the University of Copenhagen (19).…”
Section: Methodsmentioning
confidence: 99%
“…These differences include activation of channels at very negative potentials, which was never observed for cloned KCNQ channels, and the activation kinetics, which are much slower in recombinant channels (Wang et al, 1998;Kubisch et al, 1999;Schroeder et al, 2000;Sogaard et al, 2001). The molecular determinants of these differences in channel gating are currently unknown.…”
Section: Kcnq4 Currents In Ihcsmentioning
confidence: 99%